Acoustic Signal Aided Detection Method of Spiral Bevel Gears Based on PSO-MCKD - Li Xianshan; Tian Yu; Wei Lilin; Zhao Xiaofeng; Yan Changfeng (Jixie chuandong)
Aiming at the problems of cumbersome operation and strong subjectivity of the traditional detection method for the transmission accuracy of spiral bevel gears, an acoustic signal-assisted detection method for judging the transmission accuracy of spiral bevel gears is proposed. Combining the gear rolling inspection machine with the developed acoustic signal acquisition system, a real-time acoustic signal acquisition experiment is designed for detecting the quality of the contact marks on the tooth surface of the spiral bevel gear. Combined with the particle swarm optimization(PSO) algorithm and the maximum correlated kurtosis deconvolution(MCKD) based signal processing methods, the effect of different axial deviations on the gear mesh acoustic signals is investigated. It is found that the increase of the axial deviation leads to the increase of the amplitude corresponding to the mesh frequency and its octave frequency, which seriously affects the transmission accuracy of the gear. Meanwhile, the feasibility of the proposed method is verified by using practical examples, which provides an effective auxiliary mean for the detection of the meshing performance of spiral bevel gears.